Hepcidin correlates with interleukin-1β and interleukin-6 but not iron deficiency in children with Helicobacter pylori infection - Szu-Ta Chen; Yen-Hsuan Ni; Chuan-Chun Li; Shing-Hwa Liu (Pediatrics and Neonatology, 2018)
Background: Helicobacter pylori infection is associated with iron deficiency (ID) in children. Inflammatory cytokine reactions could influence the consequences of H. pylori infection. Hepcidin is an important regulator in iron homeostasis and could be induced by chronic inflammation. The relationship between hepcidin and cytokine levels in children infected with H. pylori remains controversial. Methods: Based on serology testing for anti-H. pylori IgG, participants (43 seropositive and 43 seronegative) aged 10–18 years were enrolled. Serum hepcidin levels and iron profiles, including iron, ferritin, and total iron-binding capacity, were measured. ID is defined as iron saturation less than 15%. Seropositive children were divided into low hepcidin (n = 22) and high hepcidin (n = 21) groups. IL-1β, IL-6, and IL-8 serum levels were compared. Results: Serum IL-1β and IL-6 levels were comparable between H. pylori seropositive and seronegative children, as were the median serum hepcidin levels (6.5 ng/mL versus 8.6 ng/mL; P = 0.1318). Median levels of serum iron, ferritin, and iron saturation were significantly lower in seropositive children with low hepcidin than in those with high hepcidin (P = 0.0123, P = 0.0001, and P = 0.0004, respectively). The prevalence of ID was significantly higher in those with low serum hepcidin levels (33.3% versus 4.5%; P = 0.015). Compared to the high hepcidin seropositive group, the low hepcidin group had significantly lower median serum levels of cytokines IL-1β and IL-6, but not IL-8 (P = 0.0151 and P = 0.0015, respectively). Conclusions: Inflammatory cytokines IL-1β and IL-6, but not IL-8, might be associated with increased hepcidin levels among H. pylori-seropositive children. Further studies are needed to clarify the role of hepcidin. Key Words: cytokines, Helicobacter pylori, hepcidin, IL-1 beta, iron deficiency